AJP gets GOI support, Editorial Board nominations - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
The editorial board is delighted in sharing good news with the readers and contributors of the AJP. The Department of Science and Technology, Government of India, has awarded financial support to the AJP. Although this support comes more as recognition than as finance, the latter would certainly help boost the journal further. Because the deficit of the journal is likely to be met with the provided support, the board has decided to not increase the subscription rates for the year 2010, which was on the cards. We acknowledge the efforts of Mr. DK Sharma, the Ex- Associate Editor, the award coming after his having left us.